A multi-center study on glucometabolic response to bariatric surgery for different subtypes of obesity - Liu, Yao; Sheng, Chunjun; Feng, Wenhuan; Sun, Fang; Zhang, Jingjing; Chen, Ying; Su, Lili; Liu, Jia; Du, Lei; Jia, Xuyang; You, Hui; Huang, Xiu; et al. (Frontiers in Endocrinology, 2022)
Objectives: To assess the benefit of a bariatric surgery in four artificial intelligence-identified metabolic (AIM) subtypes of obesity with respect to the improvement of glucometabolism and the remission of diabetes and hyperinsulinemia. Methods: This multicenter retrospective study prospectively collected data from five hospitals in China from 2010 to 2021. At baseline 1008 patients who underwent a bariatric surgery were enrolled (median age 31 years; median BMI 38.1kg/m2; 57.40% women) and grouped into the four AIM subtypes. Baseline and follow-up data (506 and 359 patients at 3- and 12-month post-surgery) were collected for longitudinal effect analysis. Results: Out of the four AIM subgroups, hypometabolic obesity (LMO) group was characterized by decompensated insulin secretion and high incidence of diabetes (99.2%) pre-surgery. After surgery, 62.1% of LMO patients with diabetes achieved remission, lower than the other three subgroups. Still, the bariatric surgery significantly reduced their blood glucose (median HbA1c decreased by 27.2%). The hypermetabolic obesity-hyperinsulinemia (HMO-I) group was characterized by severe insulin resistance and high incidence of hyperinsulinemia (87.8%) pre-surgery, which had been greatly alleviated post-surgery. For both metabolic healthy obesity (MHO) and hypermetabolic obesity-hyperuricemia (HMO-U) groups who showed a relatively healthy glucometabolism pre-surgery, rate of glucometabolic comorbidities improved moderately post-surgery. Conclusion: In terms of glucometabolism, the four AIM subtypes of patients benefited differently from a bariatric surgery, which significantly relieved hyperglycemia and hyperinsulinemia for the LMO and HMO-I patients, respectively. The AIM-based subtypes may help better inform clinical decisions on bariatric surgery and patient counseling pertaining to post-surgery outcomes.